+0  
 
0
33
1
avatar

x+19=y-3

2x+3=y

 Dec 25, 2018

Best Answer 

 #1
avatar+534 
+2

Substitute \(2x+3=y\) into the first equation!

 

\(x+19=2x+3-3, x+19=2x, x=19\)

Then 2(19)+3=41, so \((x, y)=(19, 41)\)

 

You are very welcome!

:P

 Dec 25, 2018
 #1
avatar+534 
+2
Best Answer

Substitute \(2x+3=y\) into the first equation!

 

\(x+19=2x+3-3, x+19=2x, x=19\)

Then 2(19)+3=41, so \((x, y)=(19, 41)\)

 

You are very welcome!

:P

CoolStuffYT Dec 25, 2018

26 Online Users

avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.